Offsetting water conservation costs to achieve net‐zero water use. Issue 2 (1st February 2013) - Olmos, Kendra C.; Loge, Frank J.
Abstract : Achieving net‐zero water use (in which annual potable water use is no greater than annual rainfall) and achieving reasonable payback periods for water conservation measures were investigated for a proposed mixed‐use housing development in Davis, Calif. Water efficiency scenarios were analyzed for indoor water use and landscape watering, along with the use of graywater and rainwater on landscaping. Potential cost savings were found in both water utility reductions associated with water conservation and energy efficiency associated with decreases in hot water use. The feasibility of selling carbon offset credits in California's new cap‐and‐trade program by reducing greenhouse gas emissions associated with the water–energy nexus was also investigated. Results indicated the feasibility of achieving net‐zero water use at the scale of a single‐family residence and the entire community through indoor and landscaping water conservation measures without the need for graywater or rainwater reuse.